Takhrij and Syarah Hadith of Agrotechnology: The Virtue of Farming - Hana Khairunnisa; Wahyudin Darmalaksana; Budy Frasetya TQ (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith of the Prophet about the Virtue of Farming. This research uses a qualitative approach of takhrij and sharah hadith with agrotechnological analysis, field studies, and literature studies. The results and discussion of agricultural research is a commendable work and there is a glory that results are not only felt by humans but also by birds, chickens, and others. The conclusion of this study is almsgiving, preserving the environment, providing food, and traditional medicinal ingredients are the benefits of farming, besides that living things also need agricultural products for food sources.